Molecular expression of recombinant Apoptin in planta and preliminary evaluation of biological characteristics of plant-made Apoptin on cancerous cells - Chan, Xiao Ying (2017)
Apoptin, a potential anticancer candidate, selectively kills tumour or transformed cells but remains harmless to normal and non-transformed cells. Besides, apoptin-induced apoptosis is independent of p53 apoptosis pathway, which is always mutated in cancer cells during tumorigenesis or after radiotherapy. This has made apoptin becoming more pharmacological valuable. In this study, the general aim was to develop a plant-derived apoptin which offers a safer and more cost-effective treatment for cancer patients. The scope of the study focused on the production of recombinant apoptin in a plant-based system and preliminary bioactivity evaluation of the purified plant-derived apoptin on human lung cancer adenocarcinoma A549 cells. Recombinant apoptin was expressed in Nicotiana benthamiana as apoptin alone, in fusion to green fluorescent protein (GFP) as well as in fusion to lichenase (Lic) to increase the expression of recombinant protein in soluble fraction. Recombinant apoptin was also in fusion to H22 single chain antibody and epidermal growth factor (EGF) in order to target recombinant H22-apoptin and EGF-apoptin to cancer cells overexpressed with immunoglobulin G (IgG) receptor (CD64) and EGF receptors. Expression of recombinant apoptin was detected in N. benthamiana successfully, however, high amount of soluble protein was obtained in plants infiltrated with recombinant GFP-apoptin (gene casette: PR-GFP-VP3-HK) and EGF-apoptin (gene casette: PR-EGF-CatAd-VP3-HK) that targeted the recombinant proteins to endoplasmic reticulum (ER). Protein purification using immobilised metal affinity chromatography (IMAC) recovered recombinant GFP-apoptin (GFP-VP3-HK) and EGF-apoptin (EGF-CatAd-VP3-HK) at a low purity when recombinant proteins were purified in a non-denaturing condition. Host cell protein contamination was not able to be removed when second chromatography and acid precipitation method were used. However, recombinant GFP-apoptin (GFP-VP3-H) and lichenase-apoptin (Lic-VP3-H) without targeted to specific cellular compartment were purified at a good purity using IMAC. Recombinant GFP-VP3-H extracted in a denaturing condition was successfully refolded without an addition of chemical additives while recombinant Lic-VP3-H required triton to refold the protein. In cell-based study, enzyme-linked immunosorbent assay (ELISA) showed that apoptin interacted with EGF receptors as well as A549 cells which finding is the first of its kind in report but with an unverified speculation. On the other hand, nuclear localisation activity and a few apoptosis-associated morphological features were observed in cells microinjected with recombinant GFP-VP3-H. Meanwhile, recombinant EGF-VP3-HK showed a dose-dependent growth inhibitory effect at higher concentration and caused the loss of mitochondrial membrane potential (MMP) in treated A549 cells. However, internalisation of recombinant EGF-VP3-HK requires a further study for confirmation. Considering the findings on MMP and caspase 3/7 assays were not convincing enough, further evaluations are necessitated in order to verify the apoptosis events induced by the recombinant GFP-VP3-H and EGF-VP3-HK. Nonetheless, this study has heralded a new milestone for apoptin research by which its protein has been successfully produced in plants and some preliminary biological characteristics have been explored at a certain extent.